CENK BLONK LEATHER PUPPET PERFORMANCE WITHIN POPULAR CULTURAL CONTEXT - Marajaya, I Made Marajaya; Suastika, I Made Suastika; Dibia, I Wayan Dibia; Ratna, I Nyoman Kutha (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2015)
This present study is intended to discuss the Cenk Blonk leather puppet performance “Wayang Kulit Cenk Blonk (abbreviated to WKCB) within the popular cultural context. If viewed from the perspective of cultural studies, this present study is concerned with a new reality and phenomenon in the Balinese puppetry art. The Balinese leather puppet performance, which does not refer to the source book of the shadow play story “pakem pewayangan” and the puppetry norm “Dharma Pewayangan”, is preferred by many people. This present study analyzes the form, factor, and meaning of the WKCB performance with the popular cultural context using the theory of popular culture, the theory of deconstruction, and theory of discourse. The qualitative interpretative method was used. The data were obtained through observation, in-depth interview, and documentary study. The data were analyzed using the descriptive, qualitative and interpretative method of analysis. The data were presented starting from the basic data, data presentation, data analysis and conclusion. The result of the study shows (1) the WKCB was performed as part of the promotional activity; (2) the WKCB was performed as part of the socialization activity; (3) the WKCB was performed as part of the commemoration of anniversaries. Second, the factors contributing to the WKCB performance within the popular cultural context included: creativity, art sustainability, the practice for the supporting artists, the modern cultural impact, the advance in technology, and the market demand. The meanings of the WKCB performance within the popular cultural context included: the aesthetic meaning, the social meaning, the welfare meaning, the amusing meaning, the political meaning, the conservation meaning, and the image meaning. The novelty shows that the WKCB performance within the popular cultural context presents the elements of popular works, popular discourses, the change in presentation, the change in the performing apparatus, and the freedom in receiving messages from those who have it performed to be transmitted to viewers.